2015
DOI: 10.5455/aim.2015.23.343-346
|View full text |Cite
|
Sign up to set email alerts
|

Interictal Electroencephalography (EEG) Findings in Children with Epilepsy and Bilateral Brain Lesions on Magnetic Resonance Imaging (MRI)

Abstract: Introduction:Neuroimaging procedures and electroencephalography (EEG) are basic parts of investigation of patients with epilepsies.Aim:The aim is to try to assess relationship between bilaterally localized brain lesions found in routine management of children with newly diagnosed epilepsy and their interictal EEG findings.Patients and methods:Total amount of 68 patients filled criteria for inclusion in the study that was performed at Neuropediatrics Department, Pediatric Hospital, University Clinical Center Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Abnormal findings using MRI were detected in 68% of patients with multifocal IED. Zubcevic et al demonstrated that 55.9% of the patients had bilateral IED in case of bilateral lesions observed by MRI, but clearly focal IED could also be observed [ 7 ]. Multifocal discharges in the present study were related to higher rates of abnormalities on the basis of the MRI findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abnormal findings using MRI were detected in 68% of patients with multifocal IED. Zubcevic et al demonstrated that 55.9% of the patients had bilateral IED in case of bilateral lesions observed by MRI, but clearly focal IED could also be observed [ 7 ]. Multifocal discharges in the present study were related to higher rates of abnormalities on the basis of the MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar with the previous reports, that indicated 55.9% bilateral epileptiform discharges in cases with bilateral lesions evidenced by brain MRI. It was postulated that some of the findings detected by MRI are not the exact cause of epilepsy but are coincidental with other abnormalities, such as hypomyelination and delayed myelination often present in patients with metabolic disorders as a cause of epilepsy [ 7 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ictal EEG recordings were considered optimal in the diagnosis of epilepsy; however, it can be challenging to acquire these recordings in real-life scenarios. As a result, interictal epileptiform activities, which are associated with epilepsy, were used as diagnostic tools [25].…”
Section: Databasesmentioning
confidence: 99%
“…These discharges may be either generalized or focal in distribution and help to classify whether a focal or generalized seizure disorder is present. 1,2 EEG can help identify seizures type and localization of epileptic focus. Also, some patterns of EEG are predictive of patients who can develop lateonset seizures, in addition, 3 epilepsy is a condition of chronic, recurring seizures and its most disabling aspect is the unpredictability of when and where the next seizure will occur.…”
Section: Introductionmentioning
confidence: 99%